ANALISA PENGENDALIAN INVENTORI MATERIAL BRACKET SIDE STAND K59A - Endang Heriansyah (Universitas Mercu Buana, 2018)
One of the most important issues in the manufacturing industry is inventory management. Inventory management control strategy affect the company performance in meeting consumer demand. In inventory management, there are two main things that concern the determination of the amount of stock and the exact time of booking. PT. XYZ is a company that produces various types of automobile spare-parts products that have not implemented maximized inventory management resulting in stockout, less productive sales, and operational operational constraints. The purpose of this study is to compare the performance of inventory management used by companies with the method POQ and min-max. Of the three methods the POQ method produces a smaller total cost, so the POQ method is recommended in the management of inventory in the company. Through the application of inventory management using the method POQ (Period Order Quantity) to generate sales productivity and managed to save the total cost of supply or obtained cost efficiency of 5.9% of the total cost or equivalent to Rp 41.558.530, 86, -.